Comparison of the base summation method versus the direct method to determine the cation exchange capacity of the soil - Gonzales-Condori, Elvis Gilmar (2024)
The cation exchange capacity (CEC) of soil is an important parameter since it is an indicator of the fertility and physicochemical quality of the soil. There are several methods to find and estimate the CEC of soils. This work aims to compare the direct ammonium distillation method and the exchangeable base summation method based on the analysis of 65 samples taken from 0 to 0.20 m depth of soils in the northern and western areas of Honduras. Initially, the analyses of pH, % organic matter, % clay, and exchangeable bases (Ca, Mg, K, and Na) extracted with ammonium acetate at pH 7.00 were carried out. In addition, they were determined by atomic absorption, exchangeable acidity (H and Al), extracted with 1N KCl determined by titration. Subsequently, the CEC was determined by direct method of soil washing and ammonium distillation. The data was subjected to Pearson correlation analysis and linear regression. The % organic matter and clay parameters did not have a significant correlation with both methods; however, the pH presented a positive correlation of r = 0.73 with the direct method and r = 0.81 with the base summation method. The Ca concentration presented positive correlations of r = 0.85 and r = 0.97 with the direct and summation method, both methods correlated positively with r = 0.86. With the data obtained, it is concluded that both methods are statistically comparable and correlate with each other to estimate the CEC of soils in northern and western Honduras.